New reconstruction for bone integration of non-vascularized autogenous bone graft with better bony union and revascularisation - Dolderer, J. H.; Geis, S.; Mueller-Wille, R.; Kelly, J. L.; Lotter, O.; Ateschrang, A.; Prantl, L.; Schiltz, D. (Archives of Orthopaedic and Trauma Surgery, 2017)
Introduction: Phalangeal defects are often seen after tumor resection, infections, and in complex open hand fractures. In many cases, reconstruction is difficult and amputation is performed to avoid prolonged rehabilitation that is often associated with a poor outcome. In these cases, the maintenance of length and function presents a reconstructive challenge. Methods: We reviewed 11 patients who underwent extensive phalangeal reconstruction with non-vascularized bone graft from the iliac crest using a key-in-slot-joint technique to provide acceptable function and bony union. Results: In each case, non-vascularized bone graft with a length of 1.4–6.0 cm was used to reconstruct the phalanx. Follow-up ranged from 6 weeks to 5 months, and in all cases, there was bony union after 6 weeks. We evaluated range of motion, function, and as well pain and grip strength of the fingers. Conclusions: This case series suggests that a key-in-slot technique allows non-vascularized bone graft to be used in complex large phalangeal bone defects. Due to better bone contact, a sufficient perfusion and revascularisation of the non-vascularized bone graft can be achieved for a quicker and stable bony union. This method appears to be an alternative to amputation in selected cases with a satisfactory soft-tissue envelope.
CRIS-Team Scopus Importer:2024-12-11
Keywords: Key-in-slot technique; Non-vascularized autogenous bone graft; Phalangeal bone defect; Phalangeal reconstruction; Revascularization